2019
DOI: 10.7150/jbji.35629
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect Of Visible Blue Light Used In A Minimally Invasive Intramedullary Fracture Stabilization System

Abstract: Introduction: Since 2009, the IlluminOss® System is being used as an intramedullary fracture treatment. The system is characterized by the use of blue light to polymerize liquid monomer after its infusion in a polyethylene terephthalate balloon. Very few infections of the material have been observed, which might be explained by the possible antimicrobial side-effect of the blue light used in this intramedullary fracture stabilization system. This study aimed to assess this antimicrobial (side-)effect on S. aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Moreover, post-operative imaging displays minimal artifacts, facilitating improved observation of tumor recurrence and bone union. In terms of basic scientific literature, there is evidence demonstrating that visible blue light emitted by the PBSS device can result in a temporary reduction of S. aureus based on in vitro testing [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, post-operative imaging displays minimal artifacts, facilitating improved observation of tumor recurrence and bone union. In terms of basic scientific literature, there is evidence demonstrating that visible blue light emitted by the PBSS device can result in a temporary reduction of S. aureus based on in vitro testing [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The infection rate seems very low in literature; it could be due to the minimal invasiveness which reduces the risk of contamination although, recently, a direct antimicrobial effect of the blue-light applied to induce polymerization was hypothesized [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if MC Sweenay et al published a study performed on rabbits in which they demonstrated the perfect compatibility of the IS-PBSS inside active bone without any significant tissue reaction and its integration, a possible limitation in the removal procedure is represented by the unique shape the nail can assume inside the patient's bone; this can make the procedure extremely aggressive from a surgical point of view. [24] The infection rate seems very low in literature; it could be due to the minimal invasiveness which reduces the risk of contamination although, recently, a direct antimicrobial effect of the blue-light applied to induce polymerization was hypothesized [25].…”
Section: Disadvantages and Complicationsmentioning
confidence: 99%
“…Also, a preliminary study on sheep provided encouraging results in the treatment of weight-bearing bone fractures [ 30 ]. The system is contraindicated in active or not completely healed infections, even if studies have been carried out on the antimicrobial effect of the light used for the polymerization of the system [ 31 ].…”
Section: Discussionmentioning
confidence: 99%